Environmental performance measurement for green supply chains: A systematic analysis and review of quantitative methods. Issue 8 (16th April 2018) - Tuni, Andrea; Rentizelas, Athanasios; Duffy, Alex
Abstract : Purpose: The majority of the environmental impacts in a typical supply chain can arise beyond the focal firm boundaries. However, no standardised method to quantify these impacts at the supply chain level currently exists. The purpose of this paper is to identify the quantitative methods developed to measure the environmental performance of supply chains and evaluate their key features. Design/methodology/approach: A systematic literature review is conducted at the intersection of performance measurement and green supply chain management (GSCM) fields, covering 78 publications in peer-reviewed academic journals. The literature is reviewed according to several perspectives, including the environmental aspects considered, the main purpose of measurement, model types and the extent of supply chain covered by performance measurements. Findings: Adopted environmental metrics show a low degree of standardisation and focus on natural resources, energy and emissions to air. The visibility and traceability of environmental aspects are still limited; the assessment of environmental impacts does not span in most cases beyond the direct business partners of the focal firms. A trade-off was observed between the range of environmental aspects and the extent of the supply chain considered with no method suitable for a holistic evaluation of the environmental supply chain performance identified. Three major streams of research developing in the field are identified, based on different scope. Originality/value: This paper is the first attempt to examine in detail what tiers of the supply chain are actually involved in green performance assessment, ultimately contributing to clarify the scope of the supply chain dimension in GSCM performance measurement research. The work also recognises which methods are applicable to extended supply chains and explores how different methodologies perform in terms of supply chain extent covered.